JavaScript Mobile Application Development. - Saleh, Hazem (Community experience distilled., 2014)
Whether you are developing a mobile app for iPad or on a Windows Phone, you need to learn the specific languages and technologies for that device. This is where Apache Cordova shines. This book is the learning resource to use when you want to efficiently develop your own mobile applications using Apache Cordova as the platform for your HTML, CSS, and JavaScript. In order to develop good-looking mobile applications, this book also utilizes jQuery Mobile. jQuery Mobile is one of the best available frameworks for developing mobile-friendly web applications. After finishing this book, you should be able to develop your very own mobile application on different mobile platforms using only JavaScript, without having to learn the native programming languages of every mobile platform.